Effect of Cryopreserved Placental Mesenchymal Stromal Cells on Pro-Inflammatory State In Experimental Type 2 Diabetes mellitus - Demin, Yuriy A.; Demina, Mariya Yu.; Shabliy, Vladimir A.; Sergienko, Andrey N. (Problems of Cryobiology and Cryomedicine, 2015)
Diabetic retinopathy is the most common microvascular complications of Diabetes mellitus and one of the leading causes of a vision loss among people of working age. In this regard, the study of pathogenesis and development of new effective methods to prevent and treat diabetic retinopathy is one of the urgent tasks of current ophthalmology. Of particular interest is the use of mesenchymal stromal cells capable of penetrating into the injury site of blood vessels and tissue ischemia as well as having an anti-inflammatory effect. The paper assessed a therapeutic efficiency of cryopreserved placental mesenchymal stromal cells (cPMSCs) in experimental diabetes induced by streptozotocin and high-calorie diet. The results demonstrated that the cPMSCs preparation had an anti-inflammatory effect manifested in reducing the concentration of C-reactive protein and tumor necrosis factor-a in the blood serum, likely contributing to the prevention of diabetic microvascular complications. Probl Cryobiol Cryomed 2015; 25(4):371-378.